2022
DOI: 10.1111/jeb.13993
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic selection on an ornamental trait is not modulated by breeding density in a pied flycatcher population

Abstract: Most studies of phenotypic selection in the wild have focussed on morphological and life‐history traits and looked at abiotic (climatic) variation as the main driver of selection. Consequently, our knowledge of the effects of biotic environmental variation on phenotypic selection on sexual traits is scarce. Population density can be considered a proxy for the intensity of intrasexual and intersexual competition and could therefore be a key factor influencing the covariation between individual fitness and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Many studies have found the intensity of sexual selection to change with population density-in one or other direction-but without any change in the direction of selection on individual traits (Conner 1989, Shuster 1989, McLain 1992, Rittschof 2010, Aronsen et al 2013, Buzatto et al 2015, Fowler-Finn et al 2017. There are other studies that failed to demonstrate any effect of population density on the intensity or direction of sexual selection (Wacker et al 2013, Morales-Mata et al 2022. In a laboratory study with Drosophila melanogaster, Sharp & Agrawal (2008) found that the intensity of sexual selection on individual genes increased with density for some genes but decreased with density for others.…”
Section: Sexual Selectionmentioning
confidence: 99%
“…Many studies have found the intensity of sexual selection to change with population density-in one or other direction-but without any change in the direction of selection on individual traits (Conner 1989, Shuster 1989, McLain 1992, Rittschof 2010, Aronsen et al 2013, Buzatto et al 2015, Fowler-Finn et al 2017. There are other studies that failed to demonstrate any effect of population density on the intensity or direction of sexual selection (Wacker et al 2013, Morales-Mata et al 2022. In a laboratory study with Drosophila melanogaster, Sharp & Agrawal (2008) found that the intensity of sexual selection on individual genes increased with density for some genes but decreased with density for others.…”
Section: Sexual Selectionmentioning
confidence: 99%
“…By contrast, the scope for sexual selection may be more limited at low densities, where infrequent mate encounters may lower a female's mate discrimination due to higher sampling costs (37)(38)(39), and rare encounters among males also limit the potential for mate competition (37). Empirical studies on these patterns, however, have yielded mixed results (9,(40)(41)(42)(43)(44)(45)(46)(47)(48). Whereas some studies point toward more intense sexual selection at higher densities (40)(41)(42), others report the opposite (44)(45)(46) or no relationship (9,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies on these patterns, however, have yielded mixed results (9,(40)(41)(42)(43)(44)(45)(46)(47)(48). Whereas some studies point toward more intense sexual selection at higher densities (40)(41)(42), others report the opposite (44)(45)(46) or no relationship (9,47,48). One possible reason for these contrasting results is that the traits examined in these studies are under pre-mating sexual selection, which might trade off with traits under post-mating sexual selection in a density-dependent manner (36,49).…”
Section: Introductionmentioning
confidence: 99%